Treatment of Traumatic Cervical Arteriovenous Fistulas with N-Butyl-2-Cyanoacrylate - Jayaraman, M.V.; Do, H.M.; Marks, M.P. (American Journal of Neuroradiology, 2007)
SUMMARY: We report 2 cases of traumatic arteriovenous fistulas in the neck treated with transarterial embolization with n-butyl-2-cyanoacrylate (n-BCA). In both cases, covered stent placement across the fistula to preserve the artery was not possible. Detachable coil placement was attempted in one case but was not successful. Both fistulas were successfully treated with n-BCA embolization. To our knowledge, these are the first 2 such cases reported of high-flow cervical arteriovenous fistulas treated with n-BCA embolization.